ANALYSIS OF THE INFLUENCE OF PRICE AND PRODUCT QUALITY ON CONSUMER PURCHASING DECISIONS FOR AUTOMOTIVE PRODUCTS (CASE STUDY: TOYOTA VS. HONDA) - Eko Sugiyanto; Yoeliastuti; Supadi Bambang (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study examines how price and product quality influence consumers’ purchasing decisions when buying Toyota and Honda cars in the Tangerang area. The research uses a quantitative approach and involves 100 respondents selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed with SPSS version 25 through various statistical tests. The results show that both price and product quality have a positive and significant effect on purchasing decisions, both individually and simultaneously. An F-value of 41.001 with a significance level of 0.000 indicates that these two factors play an important role in shaping consumer choices. In other words, competitive pricing and good product quality are the main reasons consumers choose Toyota and Honda vehicles.